The Adria Microplate: GPS Geodesy, Tectonics and Hazards - Pinter, Nicholas.; Pinter, Nicholas.; Grenerczy, Gyula.; Grenerczy, Gyula.; Weber, John.; Weber, John.; Stein, Seth.; Stein, Seth.; Medak, Damir.; Medak, Damir. (Nato Science Series: IV:, Earth and Environmental Sciences,, 2006)
Tectonic motion of the Adria microplate exerts a first-order control on the tectonics, geology, seismology, resource distribution, and the geological hazards across a broad zone of south-central Europe and the north-central Mediterranean. Since its first application to geodynamical problems, GPS geodesy has gradually revealed the nature of motion and deformation for most active areas of deformation across the Earth. One of the last remaining regional-scale problems on the planet is the motion and associated deformation in the peri-Adriatic region. Selected local-scale studies have examined aspects of this motion, but to date no truly regional analysis or regional team has systematically attacked the full breadth of this problem. A NATO Advanced Research Workshop (ARW) was held in Veszprém, Hungary from April 4-7, 2004. This workshop brought together a distinguished international group of scientists working in the peri-Adriatic region to: (1) review research activities and results, (2) share technical expertise, and (3) provide a springboard for future collaborative research on Adria geodynamics. Areas of agreement were identified, as well as remaining areas of debate. In addition, attention focused on important scientific questions and the potential for international and interdisciplinary research in the future.